(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Rohinton Mistry is an outstanding Indian-born Canadian novelist who always attempts to expose the misfortunes, oppression, and endless sufferings of women in India after Independence. In his second novel, A Fine Balance, Mistry has portrayed the predicament of marginalised women. Women are subjected to feel like slaves as they don’t have their own identity. They are tortured in the house as well as outside the house. The protagonist, Dina Dalal, strives to be an independent woman after facing a lot of violence at home. Her troubles never meet with an end and she becomes an independent individual as she runs a tailoring business. There are many other pitiable characters such as Leela, Roopa, Mrs., Gupta, and Ruby in the novel and their everlasting struggle for survival is made to study. Like Salman Rushdie, Anita Desai, Nayantara Sahgal, Khushwant Singh, Bapsi Sidhwa and Amitav Ghosh, Rohinton Mistry deftly exposes the hypocrisy and double standard of the male dominated society of Independent India.